Faktor Penyebab Penurunan Minat Belajar Peserta Didik dalam Pembelajaran Al-Qur’an di TPQ Masjid Tajul Arifin - Sirin, Muchni Zalfa; Wardefi, Riza (Lembaga Yasin AlSys, 2025)
The decline in students' interest in learning the Koran at TPQ Tajul Arifin Kapalo Mosque, Koto, Padang City is a phenomenon that needs serious attention. Interest in learning is an important factor in the success of the learning process, especially in learning the Al-Qur’an which requires seriousness and active involvement from students. This research aims to identify the factors causing the decline in students' interest in learning the Koran at TPQ. The research method used is a descriptive qualitative approach with data collection through interviews, observation and documentation. The informants in this research consisted of TPQ teachers, students, and parents of students. Data were analyzed using data reduction techniques, data presentation, and drawing conclusions. Data validity is obtained through source triangulation and technical triangulation. The results of the research show that the factors causing the decline in students' interest in learning the Al-Qur'an at TPQ Tajul Arifin Kapalo Koto Mosque include internal and external aspects. Internal factors involve low motivation to learn, lack of basic ability to read the Koran, and lack of self-awareness of students. Meanwhile, external factors include the lack of effective learning methods used by teachers, the lack of learning support facilities, and the lack of parental participation in supporting children's learning processes at home. Based on these findings, several solutions are recommended to increase students' interest in learning, such as implementing more innovative and interactive learning strategies, improving learning facilities and infrastructure, as well as increasing parental involvement in supporting Al-Qur'an learning at home. In this way, it is hoped that the TPQ Tajul Arifin Mosque can create a more conducive learning environment and be able to increase the enthusiasm of students in studying the Al-Qur'an.